Unleashing Creativity in the Classroom: Innovative Management Teaching - Uri Sternberg; Sarit Moldovan (International Journal of Educational Administration, Management, and Leadership, 2024)
This article introduces a case study of an innovative teaching approach within the context of an MBA course titled “Systematic Creative Thinking.” Leveraging the principles taught in the course, the article demonstrates the practical application of creativity theory. By incorporating templates for ideation, such as the Multiplication and Division, the course integrates diverse innovative teaching methodologies, including flipped classrooms and short videos. This approach enhances student engagement by offering personalized learning experiences. Anecdotal evidence unveiled heightened student satisfaction and performance, achieved through a synergy of theoretical comprehension and practical execution.